El Empleo Metafórico De Los Verbos De Comunicación En Los Textos Periodisticos - Nabil Ayasrah (European Scientific Journal, ESJ, 2016)
The aim of this study is to shed light on one of the linguistic mechanisms used in journalistic texts, which is the metaphorical use of verbs of communication. To achieve this goal we conducted an analysis of a corpus retrieved from the page (Royal Spanish Academy - Corpus of Current Spanish Reference CREA); we took the literal meaning of declarative verbs as it mentioned in the dictionary, and then we contemplated how journalists used these verbs metaphorically in the reproduction of some speeches from other sources. As a result, one of the fields where metaphor is frequently used is the communication verbs. The investigation led to the conclusion that enunciators use this linguistic mechanism to give the recipient some clarifications regarding the speaker and his situation when he was talking, however this process is conditional and the enunciator has to choose verbs that do not contain much ambiguity and confusion.